Benthic Habitat Mapping Using Sentinel-2A Satellite Imagery in Serewe Bay - Denianto Yoga Sativa; I Gede Nano Septian; Febrian Kusuma Atmanegara (Jurnal Biologi Tropis, 2022)
Serewe Bay is an important area for sustainable fisheries. This information on benthic habitats is important to know for sustainable management. However, at the moment there is no information on the distribution of benthic habitats in Serewe Bay. The research utilizes Sentinel 2A satellite imagery where the image used is obtained through the earthexplorer.usgs.gov website. Image data will be analyzed through several correction analysis processes, namely reflectance correction, sunglint, and water column or Lyzenga in order to obtain an image display that can be used to identify benthic habitats in Serewe Bay. In addition, a field data survey was also carried out to test the accuracy of the results of processing the Sentinel 2A satellite image of Serewe Bay. Image processing results show that there are 3 categories of benthic habitats, namely Seagrass, Sand and Mixed habitats in which there are macroalgae, dead coral, and coral fractures. The results of the field survey and accuracy calculations show that the accuracy of sentinel 2A image processing in Serewe Bay reaches 63.41% with the dominant benthic distribution consisting of seagrass, mixed benthic habitat and sand. Meanwhile, the calculation of the area of important benthic habitats such as seagrass beds in Serewe Bay can reach 156 Ha.